Enhancing Happiness Through the Feelings of Awe: Perceived Workload Affects the Relationship between Time Availability and Subjective Well-Being - Tasha, Syannia; Takwin, Bagus; Indirasari, Dyah Triarini (UI Scholars Hub, 2025)
Happiness is a state that is constantly strived for amidst the complexity of life. Previous research suggests that the student population is prone to psychological problems due to high workloads and a scarce resource of time that could affect happiness. Referring to previous studies, this study seeks to examine the relationship between feelings of awe and subjective well-being which is influenced by perceptions of time availability and perceived workload. Data were collected offline (N = 56) using VR devices to present awe-inducing videos, with responses measured via self-report. The results showed the absence of video effects on the condition of awe towards time availability (b = 0.118, p = 0.216), a positive and significant relationship was found between time availability and subjective well-being (b = 0.278, p = b = 0.412, p =